"Second Look" in the postoperative period of resections for intestinal necrosis - Matteucci, Pablo (Cirugía del Uruguay, 1979)
Prophylactic reoperations during postoperatory of intestinal necrosis resection are indicated whenever there is the smallest doubt as to intestinal vitality or suspected extension of· necrosis during postoperatory. They should be performed early, at 36 - 48 hours, before onset of symptoms indicating peritonitis. Case material consists of 3 patients with good evolution.